2016
DOI: 10.1159/000443303
|View full text |Cite
|
Sign up to set email alerts
|

Continuous End-Tidal Carbon Dioxide Monitoring during Resuscitation of Asphyxiated Term Lambs

Abstract: Background: The Neonatal Resuscitation Program (NRP) recommends close monitoring of oxygenation during the resuscitation of newborns using a pulse oximeter. However, there are no guidelines for monitoring carbon dioxide (CO2) to assess ventilation. Considering that cerebral blood flow (CBF) correlates directly with PaCO2, continuous capnography monitoring of end-tidal CO2 (ETCO2) may limit fluctuations in PaCO2 and, therefore, CBF during resuscitation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…They were intubated with a 10.0 mm-cuffed endotracheal tube (ETT) and ventilated with 21% oxygen and 2–3% isoflurane at 16 breaths/min. The ewes were continuously monitored with a pulse oximeter and an end-tidal CO 2 (EtCO 2 ) monitor [9,10]. Following cesarean section, fetal lambs were partially exteriorized and intubated with a 4.5 mm-cuffed ETT as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…They were intubated with a 10.0 mm-cuffed endotracheal tube (ETT) and ventilated with 21% oxygen and 2–3% isoflurane at 16 breaths/min. The ewes were continuously monitored with a pulse oximeter and an end-tidal CO 2 (EtCO 2 ) monitor [9,10]. Following cesarean section, fetal lambs were partially exteriorized and intubated with a 4.5 mm-cuffed ETT as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that ETCO 2 correlated well with PaCO 2 in an ovine meconium aspiration model poststabilization (11). In this study using an asphyxia model, ETCO 2 correlated well with PaCO 2 after 5 min of established ROSC.…”
Section: Discussionmentioning
confidence: 93%
“…We have previously demonstrated that use of capnography in addition to arterial carbon dioxide (PaCO 2 ) monitoring in a term lamb model of meconium aspiration resulted in maintenance of carbon dioxide in a narrower range and prevented fluctuation of carotid blood flow (11). From our pilot studies, using an asphyxiated cardiac arrest model in which active resuscitation was uninterrupted, we noted that changes in end-tidal carbon dioxide (ETCO 2 ) reflected gas exchange and also helped predict ROSC.…”
mentioning
confidence: 99%
“…We targeted preductal saturations based on current NRP recommendations ( 3 ). A respiratory monitor (NM3 Philips, Respironics, MA) with a mainstream end-tidal carbon dioxide detector (ETCO 2 ) was attached to the tracheal tube ( 13 , 14 ). Cerebral saturation was measured by NONIN (SenSmart Model X-100, Plymouth, MN) regional oximetry.…”
Section: Methodsmentioning
confidence: 99%